Discovery of novel cyclic peptide inhibitors of dengue virus NS2B-NS3 protease with antiviral activity. Issue 15 (1st August 2017) - Takagi, Youhei; Matsui, Kouhei; Nobori, Haruaki; Maeda, Haruka; Sato, Akihiko; Kurosu, Takeshi; Orba, Yasuko; Sawa, Hirofumi; Hattori, Kazunari; Higashino, Kenichi; Numata, Yoshito; Yoshida, Yutaka
Graphical abstract: Abstract: NS2B-NS3 protease is an essential enzyme for the replication of dengue virus (DENV), which continues to be a serious threat to worldwide public health. We designed and synthesized a series of cyclic peptides mimicking the substrates of this enzyme, and assayed their activity against the DENV-2 NS2B-NS3 protease. The introduction of aromatic residues at the appropriate positions and conformational restriction generated the most promising cyclic peptide with an IC50 of 0.95 μM against NS2B-NS3 protease. Cyclic peptides with proper positioning of additional arginines and aromatic residues exhibited antiviral activity against DENV. Furthermore, replacing the C-terminal amide bond of the polybasic amino acid sequence with an amino methylene moiety stabilized the cyclic peptides against hydrolysis by NS2B-NS3 protease, while maintaining their enzyme inhibitory activity and antiviral activity.